1989
DOI: 10.1111/j.1530-0277.1989.tb00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Complications of Alcoholism

Abstract: Alcohol has numerous adverse effects on the various types of blood cells and their functions. For example, heavy alcohol consumption can cause generalized suppression of blood cell production and the production of structurally abnormal blood cell precursors that cannot mature into functional cells. Alcoholics frequently have defective red blood cells that are destroyed prematurely, possibly resulting in anemia. Alcohol also interferes with the production and function of white blood cells, especially those that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
193
3
6

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(208 citation statements)
references
References 74 publications
(2 reference statements)
6
193
3
6
Order By: Relevance
“…Other nutritional anemias in alcoholics are iron deficiency anemia (often occurring) and acute spherocytic hemolytic anemia (less common) (23). The excessive alcohol consumption reduces the number of RBCs, because of direct toxic effects of alcohol including interference with maturation of them in the bone marrow (21). In our study, we also observed a decrease in the number of red blood cells in up to 64% of alcoholics.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Other nutritional anemias in alcoholics are iron deficiency anemia (often occurring) and acute spherocytic hemolytic anemia (less common) (23). The excessive alcohol consumption reduces the number of RBCs, because of direct toxic effects of alcohol including interference with maturation of them in the bone marrow (21). In our study, we also observed a decrease in the number of red blood cells in up to 64% of alcoholics.…”
Section: Discussionsupporting
confidence: 70%
“…Alcohol may cause this type of anemia by direct interference with heme synthesis. Abstinence can reverse this effect and changed sideroblasts can disappear from bone marrow within 5 to 10 d, and RBC production resume (21). Other nutritional anemias in alcoholics are iron deficiency anemia (often occurring) and acute spherocytic hemolytic anemia (less common) (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Large amounts of alcohol are known to increase blood pressure however different drinking habits seem to have different effects on blood pressure. 5 It was reported that there is a level of alcohol consumption, of approximately four drinks per day, below which drinkers have either similar or lower blood pressure levels compared to nondrinkers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, alcohol can interfere with the production and function of WBCs that defend against infections by decreasing the ability of neutrophils to bind, ingest and kill bacteria and reduce lymphocytic antibody production, as well as causing a direct toxicity on macrophages and monocytes in the BM. 5,6 Excessive alcohol use can result in thrombocytopenia due to an indirect effect of liver damage, which decreases the number of factors that are necessary for platelet formation. 6 Excessive and chronic alcohol use also puts patients at risk for additional medical comorbidities.…”
mentioning
confidence: 99%